Extraction, Purification, Sulfated Modification, and Biological Activities of Dandelion Root Polysaccharides - Xiao Wu; Na Li; Zeng Dong; Qin Yin; Tong Zhou; Lixiang Zhu; Hanxi Yan; Ziping Chen; Kefeng Zhai (Foods, 2024)
In this study, polysaccharides were extracted at a rate of 87.5% ± 1.5% from native dandelion roots, and the dandelion root polysaccharides (DRPs) were then chemically modified to obtain sulfated polysaccharides (SDRPs) with a degree of substitution of 1.49 ± 0.07. The effects of modification conditions, physicochemical characterizations, structural characteristics, antioxidant properties, hypoglycemic activity, and proliferative effects on probiotics of DRP derivatives were further investigated. Results showed that the optimum conditions for sulfation of DRPs included esterification reagents (concentrated sulfuric acid: n-butanol) ratio of 3:1, a reaction temperature of 0 °C, a reaction time of 1.5 h, and the involvement of 0.154 g of ammonium sulfate. The DRPs and SDRPs were composed of six monosaccharides, including mannose, glucosamine, rhamnose, glucose, galactose, and arabinose. Based on infrared spectra, the peaks of the characteristic absorption bands of S=O and C-O-S appeared at 1263 cm−1 and 836 cm−1. Compared with DRPs, SDRPs had a significantly lower relative molecular mass and a three-stranded helical structure. NMR analysis showed that sulfated modification mainly occurred on the hydroxyl group at C6. SDRPs underwent a chemical shift to higher field strength, with their characteristic signal peaking in the region of 1.00–1.62 ppm. Scanning electron microscopy (SEM) analysis indicated that the surface morphology of SDRPs was significantly changed. The structure of SDRPs was finer and more fragmented than DRPs. Compared with DRPs, SDRPs showed better free radical scavenging ability, higher Fe2+chelating ability, and stronger inhibition of α-glucosidase and α-amylase. In addition, SDRPs had an excellent promotional effect on the growth of Lactobacillus plantarum 10665 and Lactobacillus acidophilus. Therefore, this study could provide a theoretical basis for the development and utilization of DRPs.